Islamisasi Ilmu Dalam Upaya Mengatasi Keterbelakangan Kualitas Umat Islam Di Era Modern - Lailatus Sa’adah; Aulia Tegar Wicaksono; Della Putri Aprillianti; Muhammad Fadly Al-Ghifari; Muhamad Parhan; Syahidin Syahidin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is important human progress. Likewise, Islamic education a very important role in determining the quality of life of Muslims. Unfortunately, in this modern era it can felt that Islamic education is lagging behind modern western. According to Al-Faruqi, this is evidenced by existence of identity crisis, loss of economic, political and intellectual independence in Islamic world, existence of sectarianism that focuses on borders, and slow modernization (Ramdhani, 2013 ). There are factors that cause these things, namely: the influence of western science and philosophy, colonialism, lack of Islamic unity, and lack of modernization of Islamic. To overcome these problems, ulama proposed the Islamization of science. This article was created using the SLR method. It aims to integrate Islamic principles and values into field of science and knowledge which involves a process of rethinking, re-evaluating and reconstructing scientific knowledge to enrich the vision and struggle of Islam (Sahide, 2015). The concept of Islamization of Science was introduced by Ismail Raji Al-Faruqi who defined it as an effort to integrate science into the unity of Muslim life with aims to improve the quality of Islamic education, and hoped it can also improve the quality of life of Muslims in this era.